Development of new methodologies for the chromogenic estimation of betrixaban concentrations in plasma. (3rd January 2019) - Siriez, Romain; Evrard, Jonathan; Dogné, Jean‐Michel; Pochet, Lionel; Bouvy, Céline; Lessire, Sarah; Mullier, François; Douxfils, Jonathan
Abstract: Introduction: Chromogenic anti‐Xa assays are the most appropriate tests to estimate the amount of betrixaban in plasma but the sensitivity of available tests is limited and improvements are needed to encompass the on‐therapy range. Methods: Betrixaban was spiked at concentrations ranging from 0 to 500 ng/mL in plasma from healthy donors. Three commercial tests were used (Biophen ® DiXaI ®, STA ® Liquid Anti‐Xa, and HemosIL ® Liquid Anti‐Xa), and adaptation of their sample dilution scheme was performed. These new methodologies were also tested on plasma spiked with amounts of unfractionated heparin (UFH), low molecular weight heparins (LMWH), or fondaparinux covering the on‐therapy ranges to evaluate their sensitivity to indirect factor Xa inhibitors. Results: Results showed concentration‐dependent decreases in OD/min inversely proportional to the dilutions. While modifications improve the sensitivity of these tests to betrixaban (eg, ½*OD/min of 502 ng/mL [95% CI: 495‐508 ng/mL] for Biophen ® DiXaI ® [1:50] is reduced to 51 ng/mL [95% CI: 50‐52 ng/mL] for improved Biophen ® DiXaI ® [1:5]), results also showed an increased sensitivity to indirect factor Xa inhibitors, except for Biophen ® DiXaI ® which remains insensitive to UFH and LMWH. Conclusions: Results showed that the improvement of current chromogenic anti‐Xa methodologies enhances the sensitivity of these assays to betrixaban but also to indirect factor Xa inhibitors. This lack of specificity may lead to overestimation of betrixaban concentrations in patients bridged with heparins. To avoid this cross‐interference, the use of the Biophen ® DiXaI ® may be a solution except for fondaparinux which remains active even in the presence of the Biophen ® DiXaI ® 's specific buffer. For the other chromogenic assays, the conception and validation of specific buffer is required.